OCA cubes: Mundell in 3D - Michaela Krčílková; Jan Zápal (Charles University in Prague, Institute of Economic Studies (IES), 2009)
This paper intends to fill two gaps in the Optimal Currency Area literature. First of all, Mundell's original idea has very little formalmodel theoretical underpinning. Second, it almost exclusively views countries contemplating monetary unification as single economies. We question this view and expand the model to incorporate the division of an economy into three sectors. In the empirical part of the paper, we follow recent OCA empirici literature and investigate the correlation of shocks between the individual new EU member countries and the 'EU-core'. Treating the whole economy as one sector this is a standard exercise. However, since the threesector version of our model provides a natural metric on which to assess the appropriateness of unification, we are able to repeat the exercise treating each country's economy as a collection of three distinct sectors. In the paper we test for the different reactions of stock markets to the current financial crisis. We focus on Central European stock markets, namely the Czech, Polish and Hungarian ones, and compare them to the German and U.S. benchmark stock markets. Using wavelet analysis, we decompose a time series into frequency components called scales and measure their energy contribution. The energy of a scale is proportional to its wavelet variance. The decompositions of the tested stock markets show changes in the energies on the scales during the current financial crisis. The results indicate that each of the tested stock markets reacted differently to the current financial crisis. More important, Central European stock markets seem to have strongly different behaviour during the crisis.
Keywords: E32; F15; F40; 330; OCA; supply and demand shocks; VAR decomposition; new EU member states; Optimaler Währungsraum; Eurozone; EU-Erweiterung; Schock; EU-Staaten (Osteuropa); EU-Staaten